2019
DOI: 10.1177/2059799119863280
|View full text |Cite
|
Sign up to set email alerts
|

Self-interpreted narrative capture: A research project to examine life courses of Amerasians in Vietnam and the United States

Abstract: When American troops withdrew from Vietnam in April 1975, they left behind a large number of children fathered by American GIs and born to local Vietnamese women. Although there is some documentation of experiences of GI children who immigrated to the United States, little is known about the life courses of Amerasian children who remained in Vietnam, and no comparative data has been collected. To address this knowledge gap, we used an innovative mixed qualitative – quantitative data collection tool, Cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Our study showed that people who grew up as GOC predominantly benefited from the attention they received as part of the process of participating in the study (interest in their life story, removal of taboos, acknowledgment of specific living conditions and associated challenges, having their say, being seen). This phenomenon has been described as the participants' "genuine need to 'have their voices heard"' , and has been reported of other CBOW populations as well (e.g., Lee and Bartels, 2019a). Moreover, our findings are in line with studies on risks and benefits in (trauma) research participation, stating that despite a possible negative emotional reaction during the study protocol, the majority reported beneficial aspects resulting from participation.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that people who grew up as GOC predominantly benefited from the attention they received as part of the process of participating in the study (interest in their life story, removal of taboos, acknowledgment of specific living conditions and associated challenges, having their say, being seen). This phenomenon has been described as the participants' "genuine need to 'have their voices heard"' , and has been reported of other CBOW populations as well (e.g., Lee and Bartels, 2019a). Moreover, our findings are in line with studies on risks and benefits in (trauma) research participation, stating that despite a possible negative emotional reaction during the study protocol, the majority reported beneficial aspects resulting from participation.…”
Section: Discussionsupporting
confidence: 89%
“…Our cross-sectional, mixed qualitative-quantitative two-country study was conducted in 2017 (Lee and Bartels, 2019). Data collection in Vietnam occurred in April and May in collaboration with the Department of Anthropology at the University of Social Sciences & Humanities at the Vietnam National University in Ho Chi Minh City.…”
Section: Research Partnersmentioning
confidence: 99%